Evaluation of an Instructional Video and Simulation Model for Teaching Slit Lamp Examination to Medical Students - Collis, Sophia; Yung, Madeline; Parikh, Neeti (Journal of Academic Ophthalmology, 2023)
Purpose This article assesses the efficacy of an instructional video and model eye simulation for teaching slit lamp exam to medical students as compared to traditional preceptor teaching.Methods First through 4th year students from the University of California, San Francisco School of Medicine were recruited via email to participate in the study. Students were randomized into two groups. The experimental “model eye” group watched an instructional video on slit lamp exam, spent 10 minutes practicing on the model eye, then practiced for 25 minutes with a student partner. The control “preceptor teaching” group received 25 minutes of in-person preceptor teaching on slit lamp exam, then spent 25 minutes practicing with a student partner. Students were objectively assessed by a blinded grader who scored their examination skills with a 31-item checklist. Qualtrics surveys that measured student perceptions were distributed before and after the intervention.Results Seventeen medical students participated in the study. Students in the model eye group achieved higher mean objective assessment scores than students in the preceptor teaching group on skills relating to slit lamp set up (1.75, standard deviation [SD] = 0.50 and 1.50, SD = 0.80 out of 2 points, p = 0.03) and on the total score (1.69, SD = 0.6 and 1.48, SD = 0.8 out of 2 points, p < 0.01). Both groups reported a significant increase in their understanding of what a slit lamp is used for (p < 0.01) and in their confidence using a slit lamp (p < 0.01). All students felt their skills improved with the workshop, 94% found the workshop to be useful, and 88% enjoyed the workshop, with no intergroup differences on these metrics.Conclusion An instructional video combined with a simulation model is as effective as traditional preceptor teaching of the slit lamp exam. Such a teaching module may be considered as an adjunct to traditional methods.
Keywords: medical student education; slit lamp; video-based learning; simulation